Pengaruh Kualitas Pelayanan dan Fasilitas Perpustakaan terhadap Kepuasan Pengguna di Institut Agama Islam Nasional Laa Roiba Bogor - Heni Feviasari; Imam Tholkhah; Efrita Norman (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
This study discusses the quality of service and library facilities on user satisfaction at the National Islamic Institute of Religion Library Laa Roiba Bogor based on the opinions of library users. The method used is quantitative, the population in this study is library visitors, namely students of the National Islamic Institute of Islam Laa Roiba as many as 355 people. This population is obtained from the number of library visitors. The type of sample selection in this study uses simple random sampling, where the sampling of members of the population is carried out randomly without regard to the existing strata in the population. In determining the number of samples using the Slovin formula. With the Slovin formula, it is known that the sample is 78 people. Based on the results of the study, according to library users, the quality of service and library facilities at the Laa Roiba National Islamic Institute Library got a good score. This is evidenced by the results of regression analysis that the correlation coefficient of service quality competence and library facilities is positive. Keywords: Service Quality, Library Facilities, User Satisfaction